2010
DOI: 10.1002/ejic.201000643
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deposition of Gold Nanoparticles on or Inside Carbon Nanotubes and Their Catalytic Activity for Preferential Oxidation of CO

Abstract: Gold nanoparticles have been deposited on three kinds of carbon nanotubes (CNTs), including nitrogen‐doped CNTs, by three different methods, namely, impregnation, organometallic decomposition, and deposition–precipitation. The choice of the gold precursor, the support, and the preparation procedure is critical for the control of the size and location (on or inside the nanotubes) of the gold nanoparticles. These catalysts were tested for the selective oxidation of CO in a hydrogen‐rich atmosphere. We have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…CNTs have been widely studied as supports for nanoscopic metal catalysts, although those were generally deposited on the outer surface [11][12][13][14][15][16][17][18][19][20][21][22][23]. A few studies [16,18,20,23] show the reactions catalyzed by metal NPs encapsulated inner cavity of the CNTs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…CNTs have been widely studied as supports for nanoscopic metal catalysts, although those were generally deposited on the outer surface [11][12][13][14][15][16][17][18][19][20][21][22][23]. A few studies [16,18,20,23] show the reactions catalyzed by metal NPs encapsulated inner cavity of the CNTs.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies [16,18,20,23] show the reactions catalyzed by metal NPs encapsulated inner cavity of the CNTs. The earlier studies have revealed that Pd NPs could be introduced inside multi-walled CNTs by an incipient wetness impregnation technique [16,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Au NPs have been deposited on NCNTs by Castillejos et al [455] using deposition-precipitation method starting from a water/methanol solution of sodium tetrachloroaurate(III) that is added to NCNTs, and the resulting precipitate was dried at 100…”
Section: Preparation Of Metal/ncnts Compositesmentioning
confidence: 99%